Preparation method of multi-element doped asphalt-based hard carbon material for negative electrode of sodium-ion battery and battery
The multi-doped asphalt-based hard carbon material prepared through multi-doping and cross-linking technology solves the problem of capacity attenuation of sodium ion battery hard carbon materials at high magnifications, achieving high specific capacity, excellent rate performance and high first-time Coulomb efficiency The comprehensive improvement meets the demand for power batteries.
Patent Information
- Application Number
- CN202411783319.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing sodium ion battery hard carbon materials have rapidly attenuated their capacity under high rate current density, which cannot take into account both high specific capacity and rate performance. The first time Coulomb efficiency is not ideal, making it difficult to meet the power and energy storage needs.
Through multi-doping and cross-linking technology, a multi-doping asphalt-based hard carbon material is prepared. The specific steps include pre-oxidation of asphalt and zinc organic acid, mixing with cross-linking agents containing N and P and high-temperature carbonization to form a high layer with high layers Hard carbon materials with spacing and short-range ordered structures.
It has achieved a comprehensive performance improvement of hard carbon materials with high capacity retention rate, high Coulomb efficiency and excellent rate performance at high magnification, which can meet the needs of power batteries.
Smart Images

Figure CN119461333A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a preparation method and application of a multi-element doped asphalt-based hard carbon material. Background Art
[0002] Sodium-ion batteries are generally considered to be the best choice to replace lithium-ion batteries in the field of new energy because the resources of metallic sodium are more abundant and cheaper than lithium, and they have a lower decomposition potential. However, since the ion radius of Na is larger than that of Li, the click material migrates slowly, the deintercalation process is complicated, and the reversible capacity and rate performance are not ideal and cannot meet actual needs. Graphite negative electrode materials widely used in lithium-ion batteries are not suitable for sodium-ion batteries. Na + The ions are large, and the intercalation compounds formed with carbon are thermodynamically unstable and difficult to embed into the graphite layer. At present, hard carbon materials are recognized as negative electrode materials suitable for sodium ion batteries, and the best possible commercial production. Compared with soft carbon materials, which are all amorphous carbon, hard carbon materials are carbon materials that will not be converted into graphite at high temperatures above 3000°C. The raw materials of hard carbon materials are widely available, including biomass, fossil fuels, and polymer resins, and the preparation process is relatively simple, so they have attracted much attention from researchers. However, compared with traditional negative electrode materials such as graphite, hard carbon materials are short-range ordered structures with low electrical conductivity, which affects the rate performance and first coulomb efficiency; in addition, there are a large number of micropores and defects inside hard carbon materials, and the complexity and unevenness of the structure make it difficult for active materials to fully utilize their capacity. Existing hard carbon materials make the voltage hysteresis obvious during high-rate charge and discharge, resulting in the voltage corresponding to the full battery platform capacity being lower than the deposition voltage of metallic sodium. Therefore, it is often difficult to balance high specific capacity and rate performance. At high current density, the capacity will decay rapidly, which cannot meet the requirements of current high-power batteries, especially batteries for new energy vehicles.
[0003] In order to increase the conductivity of hard carbon materials, there are existing technologies to add nanostructured materials such as carbon nanotubes and graphene to build efficient conductive channels, but the support cost is greatly increased, the advantage of low cost of hard carbon materials is lost, and it is difficult to produce commercially. Doping is an effective method to improve hard carbon materials. CN115849372A discloses an active hard carbon material, which is to polycondense 5-dipyridoyl chloride and 4-(4-aminophenyl)-2,6-bis(4-aminophenyl)pyridine to obtain a pyridine-based porous polymer, high temperature carbonization, nitrogen doping in carbon materials to form active structures such as pyridine N, improve the degree of graphitization of carbon materials, and have higher conductivity and electrochemical properties. However, its process is complicated, and the raw material is a polymer obtained by polycondensation of monomers under a catalyst, and the manufacturing cost is high. CN118771353A discloses an oxygen-doped hard carbon electrode material, comprising dissolving an asphalt carbon source and a cross-linking agent in an epoxy organic solvent, adding a catalyst, and heating to obtain a mixed solution; adding an alkaline solution to the mixed solution to perform a cross-linking reaction, and obtaining a cross-linked solid after drying; placing the cross-linked solid in a hydrogen-argon mixed atmosphere and heating to obtain a pre-treated cross-linked solid; and annealing the original treated cross-linked solid to obtain the oxygen-doped hard carbon electrode material.
[0004] However, the hard carbon materials provided by the above-mentioned existing technologies still cannot take into account the specific capacity, rate performance and first coulombic efficiency, and cannot meet the requirements of power and energy storage sodium ion batteries. Summary of the invention
[0005] In order to overcome the problem that the electrochemical performance of sodium ion battery hard carbon materials in the prior art cannot meet the actual requirements, especially the problem that the specific capacity, rate performance and first coulombic efficiency cannot be taken into account. The present invention proposes a preparation method and application of a multi-element doped asphalt-based hard carbon material. The present invention is achieved by the technical means of multi-element doping and cross-linking, and has high specific capacity and rate performance, high capacity retention rate at high rate current density, and high first coulombic efficiency to meet the current growing demand for batteries, especially power batteries.
[0006] Specifically, the present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] A method for preparing a multi-component doped pitch-based hard carbon material comprises the following steps:
[0008] (S1) asphalt and zinc salt of an organic acid are mixed and crushed, and then pre-oxidized in an oxygen-containing atmosphere to obtain pre-oxidized asphalt particles;
[0009] (S2) pre-oxidized asphalt particles, N-containing aromatic polyaldehyde, and hydroxyethylidene diphosphoric acid are uniformly mixed, and heated to react under an inert atmosphere to obtain modified asphalt particles;
[0010] (S3) Under an inert atmosphere, the modified asphalt particles are carbonized at high temperature to obtain a multi-component doped asphalt-based hard carbon material.
[0011] Furthermore, in step (S1), the asphalt is selected from at least one of petroleum asphalt, coal asphalt, and biomass asphalt, and the softening point of the asphalt is 100-160°C; the organic acid zinc is selected from at least one of zinc gluconate, zinc tartrate, zinc citrate, and zinc malate, preferably zinc tartrate.
[0012] Furthermore, in step (S1), the amount of organic acid zinc is 10-20wt% of the asphalt. The crushing method is not particularly limited, and the asphalt can be made into microspheres of 5-20 μm, for example, by ball milling.
[0013] The organic acid zinc added in the present invention can achieve multiple functions. On the one hand, the organic acid zinc is rich in oxygen atoms, which can enhance the oxidation efficiency and form more abundant oxygen-containing functional groups in the pre-oxidation step. In addition, the inventors unexpectedly found that the introduction of organic acid zinc can inhibit the degree of high-temperature carbonization and graphitization, and the product has a higher degree of defects and an increased disorder, which is conducive to increasing the interlayer spacing of the obtained hard carbon material. The possible reason is that the product after pyrolysis of organic acid zinc has a certain catalytic aromatization ability during the high-temperature carbonization process.
[0014] Furthermore, in step (S1), the oxygen-containing atmosphere is an atmosphere with an oxygen volume content of more than 20%, such as oxygen or air. The pre-oxidation temperature is 180-240° C., and the pre-oxidation time is 3-5 hours.
[0015] Pre-oxidation introduces oxygen defects, which break the ordered structure of the asphalt. In the subsequent high-temperature carbonization process, a short-range ordered structure can be formed, which inhibits the graphitization tendency of carbon atom rearrangement at high temperature. In addition, oxygen-containing functional groups are introduced into the asphalt after pre-oxidation, which is more conducive to the subsequent cross-linking step.
[0016] Furthermore, in step (S2), the N-containing aromatic polyaldehyde is at least one of 1,3,5-tris(4-formylphenyl)-2,4,6-triazine, (3,3'-bipyridine)-6,6'-dicarboxaldehyde, and pyridine-2,6-dicarboxaldehyde.
[0017] Furthermore, in step (S2), the mass ratio of the pre-oxidized asphalt particles, the N-containing aromatic polyaldehyde, and the hydroxyethylidene diphosphoric acid is 100:5-8:3-6. There is no particular limitation on the method of uniform mixing, such as high-speed mixing, ball milling. Ball milling is preferred. The inert atmosphere is nitrogen and / or argon.
[0018] Furthermore, in step (S2), the temperature is raised to 200-300°C for 2-3h. The N-containing aromatic polyaldehyde acts as a crosslinking agent on the one hand and introduces doped N on the other hand; similarly, hydroxyethylidene diphosphonic acid acts as a crosslinking agent on the one hand and introduces doped P on the other hand. The present invention introduces doped oxygen in the pre-oxidation step and introduces doped N and doped phosphorus in step (S2) to form a multi-doping of the hard carbon material. The multi-doping of O, N, and P plays a synergistic role and works together to improve the electrochemical properties of the hard carbon material. Crosslinking is beneficial to the transformation of long-range order into short-range ordered structure after high-temperature carbonization, and can inhibit the rearrangement of carbon during high-temperature carbonization; at the same time, the introduction of N and P also reduces the degree of order of the hard carbon material and introduces more defects.
[0019] Furthermore, in step (S3), high-temperature carbonization is carried out by heating the temperature to 800-1100°C at a heating rate of 1-3°C / min, pre-carbonizing for 1-2 hours, then heating the temperature to 1100-1600°C at a heating rate of 1-10°C / min, pre-carbonizing for 2-5 hours, cooling to room temperature, and sieving to obtain the product multi-doped asphalt-based hard carbon material.
[0020] The hard carbon material prepared by the above preparation method is modified by multi-element doping, and the active sites with Na ions are increased, which inhibits the graphitization accumulation of high-temperature carbonization, is beneficial to increase the interlayer spacing, and enhances the sodium storage capacity of the material at high rates. It has excellent electrochemical properties, high specific capacity, high first coulombic efficiency, excellent rate performance and cycle stability.
[0021] The present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the above-mentioned multinary doped asphalt-based hard carbon material.
[0022] The present invention optimizes the preparation process reasonably. First, the asphalt precursor and the organic acid zinc are mixed and pre-oxidized to reduce the hydrogen content in the precursor, increase the softening point, and increase the oxygen-containing functional groups; then, a cross-linking agent containing N and P is added for cross-linking. The cross-linking agent plays a multi-functional role, that is, it has a cross-linking effect, and N and P are doped into the hard carbon material. The presence of these heteroatoms can reduce the rearrangement of carbon atoms in the carbonization process, inhibit the tendency of graphitization, and make the obtained hard carbon material have a short-range ordered structure, and the sodium storage capacity and sodium ion transmission capacity are improved. The hard carbon material obtained by the preparation method of the present invention has a high specific capacity and first coulomb efficiency, and the rate performance is also improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a SEM image of the hard carbon material obtained in Example 1.
[0024] Figure 2 This is a TEM image of the hard carbon material obtained in Example 1.
[0025] Figure 3 is the XRD pattern of the hard carbon material obtained in Example. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0027] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0028] The petroleum asphalt used in the embodiment of the present invention has a softening point of 120°C.
[0029] Example 1
[0030] (S1) 100 parts by mass of petroleum asphalt and 10 parts by mass of zinc tartrate are mixed by ball milling, and the ball milling conditions are a ball-to-material ratio of 20:1, a rotation speed of 300 rpm, and a ball milling time of 2 h to obtain a spherical material with a particle size of about 15 μm. The material obtained after ball milling is heated to 200° C. in an air atmosphere for pre-oxidation for 3 h to obtain pre-oxidized asphalt particles;
[0031] (S2) 100 parts by weight of pre-oxidized asphalt particles, 5 parts by weight of 1,3,5-tris(4-formylphenyl)-2,4,6-triazine, and 5 parts by weight of hydroxyethylidene diphosphonic acid are mixed uniformly by ball milling, and the mixture is heated to 260° C. for reaction for 3 hours under a nitrogen atmosphere to obtain modified asphalt particles;
[0032] (S3) In a nitrogen atmosphere, the modified asphalt particles are subjected to high-temperature carbonization. The high-temperature carbonization is first slowly heated to 1000°C at a heating rate of 3°C / min, kept warm for pre-carbonization for 1 hour, then heated to 1400°C at a heating rate of 10°C / min, kept warm for 3 hours, cooled and sieved to obtain the product multi-component doped asphalt-based hard carbon material.
[0033] Figure 1 is a SEM image of the hard carbon material obtained in Example 1. Figure 2 This is a TEM image of the hard carbon material obtained in Example 1. Figure 3 is the XRD pattern of the hard carbon material obtained in Example. Figure 3 The XRD pattern shows that the (002) interlayer spacing is 0.385 nm.
[0034] Example 2
[0035] (S1) 100 parts by mass of petroleum asphalt and 20 parts by mass of zinc gluconate are mixed by ball milling, and the ball milling conditions are a ball-to-material ratio of 20:1, a rotation speed of 300 rpm, and a ball milling time of 2 h to obtain a spherical material with a particle size of about 15 μm. The material obtained after ball milling is heated to 200° C. in an air atmosphere for pre-oxidation for 5 h to obtain pre-oxidized asphalt particles;
[0036] (S2) 100 parts by weight of pre-oxidized asphalt particles, 8 parts by weight of 1,3,5-tris(4-formylphenyl)-2,4,6-triazine, and 6 parts by weight of hydroxyethylidene diphosphonic acid are mixed uniformly by ball milling, and the mixture is heated to 300° C. for reaction for 2 h under a nitrogen atmosphere to obtain modified asphalt particles;
[0037] (S3) In a nitrogen atmosphere, the modified asphalt particles are subjected to high-temperature carbonization. The high-temperature carbonization is first slowly heated to 800°C at a heating rate of 3°C / min, kept warm for pre-carbonization for 2 hours, then heated to 1400°C at a heating rate of 10°C / min, kept warm for 3 hours, cooled and sieved to obtain the product multi-component doped asphalt-based hard carbon material.
[0038] Example 3
[0039] The other conditions are the same as those in Example 1, except that in step (S2), 1,3,5-tris(4-formylphenyl)-2,4,6-triazine is replaced by an equal amount of (3,3'-bipyridine)-6,6'-dicarboxaldehyde.
[0040] Example 4
[0041] The other conditions are the same as those in Example 1, except that in step (S2), 1,3,5-tris(4-formylphenyl)-2,4,6-triazine is replaced by an equal mass of pyridine-2,6-dicarboxaldehyde.
[0042] Example 5
[0043] The other conditions were the same as those in Example 1, except that in step (S3), after pre-carbonization by heat preservation, the temperature was raised to 1100° C. at a rate of 10° C. / min and kept at this temperature for 3 h.
[0044] Example 6
[0045] The other conditions are the same as those in Example 1, except that in step (S3), after pre-carbonization by heat preservation, the temperature is increased to 1500° C. at a rate of 10° C. / min and kept at this temperature for 3 h.
[0046] Example 7
[0047] The other conditions are the same as those in Example 1, except that in step (S3), after pre-carbonization by heat preservation, the temperature is raised to 1600°C at a rate of 10°C / min and kept at this temperature for 3h.
[0048] Comparative Example 1
[0049] Other conditions and operations were the same as those in Example 1, except that in step (S1), zinc tartrate was replaced by magnesium tartrate.
[0050] Comparative Example 2
[0051] The other conditions and operations are the same as those in Example 1, except that in step (S1), after the petroleum asphalt and zinc tartrate are ball-milled and mixed, the resulting material is directly subjected to step (S2), i.e., the step of heating pre-oxidation under air in step (S1) is eliminated.
[0052] Comparative Example 3
[0053] Other conditions and operations are the same as those in Example 1, except that in step (S2), 1,3,5-tris(4-formylphenyl)-2,4,6-triazine is replaced by an equal mass of terephthalaldehyde.
[0054] Comparative Example 4
[0055] Other conditions and operations are the same as those in Example 1, except that in step (S2), hydroxyethylidene diphosphonic acid is not added.
[0056] Application Examples
[0057] The hard carbon materials prepared in the above examples and comparative examples were assembled into a sodium ion battery. Specifically, the hard carbon material, PVDF, and carbon black were added to a solvent N-methylpyrrolidone in a mass ratio of 90:7:3 to prepare a slurry, and the slurry was coated on a copper foil current collector so that the loading amount of the hard carbon material on the copper foil current collector was 1 mg / cm 2 , made into negative electrode; sodium sheet as counter electrode, EC:DMC volume ratio 1:1 as electrolyte, 1mol / L NaPF6 as electrolyte, assembled into 2032 button cells in a glove box filled with argon, after assembly, let stand for 8h at 25±2℃, test electrochemical performance, the results are shown in Table 1. The charge and discharge cycle voltage range is 0.01V-2.5V.
[0058] Table 1 Electrochemical performance test
[0059]
[0060]
Claims
1. A method for preparing a multi-element doped asphalt-based hard carbon material for a negative electrode of a sodium ion battery, characterized in that: The following steps are involved: (S1) asphalt and zinc salt of an organic acid are mixed and crushed, and then pre-oxidized in an oxygen-containing atmosphere to obtain pre-oxidized asphalt particles; (S2) pre-oxidized asphalt particles, N-containing aromatic polyaldehyde, and hydroxyethylidene diphosphoric acid are uniformly mixed, and heated to react under an inert atmosphere to obtain modified asphalt particles; (S3) Under an inert atmosphere, the modified asphalt particles are carbonized at high temperature to obtain a multi-component doped asphalt-based hard carbon material.
2. The preparation method according to claim 1, characterized in that: In step (S1), the asphalt is selected from at least one of petroleum asphalt, coal asphalt and biomass asphalt, and the softening point of the asphalt is 100-160°C.
3. The preparation method according to claim 1, characterized in that: In step (S1), the organic acid zinc is selected from at least one of zinc gluconate, zinc tartrate, zinc citrate and zinc malate, preferably zinc tartrate.
4. The preparation method according to claim 1, characterized in that: In step (S1), the amount of organic acid zinc used is 10-20wt% of the asphalt.
5. The preparation method according to claim 1, characterized in that: In step (S1), in step (S1), the oxygen-containing atmosphere is an atmosphere with an oxygen volume content of more than 20%; the pre-oxidation temperature is 180-240° C., and the pre-oxidation time is 3-5 hours.
6. The preparation method according to claim 1, characterized in that: In step (S1), in step (S2), the N-containing aromatic polyaldehyde is at least one of 1,3,5-tris(4-formylphenyl)-2,4,6-triazine, (3,3'-bipyridine)-6,6'-dicarboxaldehyde, and pyridine-2,6-dicarboxaldehyde.
7. The preparation method according to claim 1, characterized in that: In step (S1) and step (S2), the mass ratio of pre-oxidized asphalt particles, N-containing aromatic polyaldehyde, and hydroxyethylidene diphosphoric acid is 100:5-8:3-6.
8. The preparation method according to claim 1, characterized in that: In step (S2), the temperature is raised to 200-300° C. for 2-3 hours.
9. The preparation method according to claim 1, characterized in that: In step (S3), high-temperature carbonization is carried out by heating the temperature to 800-1100°C at a heating rate of 1-3°C / min, pre-carbonizing for 1-2 hours, then heating the temperature to 1100-1600°C at a heating rate of 1-10°C / min, pre-carbonizing for 2-5 hours, cooling to room temperature, and sieving to obtain a product multi-doped asphalt-based hard carbon material.
10. A sodium ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that: The negative electrode comprises a hard carbon material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation of active hard carbon material and application of active hard carbon material in sodium ion battery
CN115849372A
Oxygen-doped hard carbon electrode material for sodium ion battery as well as preparation method and application of oxygen-doped hard carbon electrode material
CN118771353A
Preparation method of heteroatom-doped silicon-carbon negative electrode material and material thereof
CN114566637A
Asphalt-based hard carbon negative electrode material, preparation method and sodium ion battery
CN115611264A
P and O co-doped sodium ion battery hard carbon negative electrode material and preparation method thereof
CN117163940A
Cited By
Preparation method of hard carbon material with improved high rate capability for sodium ion battery
CN120246983A
Preparation method of modified asphalt-based hard carbon microspheres for negative electrode of sodium-ion battery
CN120246986A
Hard carbon negative electrode material and preparation method and application thereof
CN120398033A